2011
DOI: 10.1158/1078-0432.ccr-10-1302
|View full text |Cite
|
Sign up to set email alerts
|

The Histone Methyltransferase and Putative Oncoprotein MMSET Is Overexpressed in a Large Variety of Human Tumors

Abstract: Purpose: Multiple myeloma SET (Suppressor of variegation, Enhancer of zeste, and Trithorax) domain (MMSET) is a histone lysine methyltransferase deregulated in a subgroup of multiple myelomas with the t(4;14)(p16;q32) translocation and poor prognosis. With the aim of understanding, if MMSET can be involved in other types of cancer we investigated the expression of MMSET protein in different types of human tumors.Experimental Design: A monoclonal antibody against MMSET was developed and immunohistochemical stai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
119
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(121 citation statements)
references
References 33 publications
(48 reference statements)
2
119
0
Order By: Relevance
“…Furthermore, dosage sensitivity of WHSC1 (also known as MMSET/NSD2) is supported by its overexpression in a variety of cancer types. 34,35 These findings suggest WHSC1 haploinsufficiency may contribute to the growth and developmental delays of patients 1-3, and perhaps also to variably present minor malformations, immunologic findings and mild dysmorphic features.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, dosage sensitivity of WHSC1 (also known as MMSET/NSD2) is supported by its overexpression in a variety of cancer types. 34,35 These findings suggest WHSC1 haploinsufficiency may contribute to the growth and developmental delays of patients 1-3, and perhaps also to variably present minor malformations, immunologic findings and mild dysmorphic features.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, NSD2 is overexpressed in neuroblastoma, lung, colon and bladder cancer [61,62], and is required for proliferation of neuroblastoma cells and brain-derived neural stem cells [62]. An E1099K mutation in the SET domain of 1594 Future Med.…”
Section: H3k36me3mentioning
confidence: 99%
“…Indeed, NSD2 is overexpressed in neuroblastoma, lung, colon and bladder cancer [61,62], and is required for proliferation of neuroblastoma cells and brain-derived neural stem cells [62]. An E1099K mutation in the SET domain of future science group Review Rogawski, Grembecka & Cierpicki NSD2 was identified in a range of human cancer cell lines and tumor samples, including acute lymphoblastic leukemia, chronic lymphocytic leukemia, lung cancer and stomach cancer [63,64].…”
mentioning
confidence: 99%
“…Histone lysine methyltransferases (HMTases) are transcriptional coregulators that target specific lysines on histones H3 and H4, and can transfer up to three methyl groups (Kme1, Kme2, and Kme3) [1]. However, the molecular mechanisms of histone mark recognition remain unclear [2][3][4][5][6]. Epigenetic marks on H3K4, H3K9, H3K27, H3K36, H3K79, and H4K20 have been reported to play primary roles in regulating the chromatin and contribute to the histone code that is still obscure [7].…”
Section: Introductionmentioning
confidence: 99%
“…The NSD proteins are oncogenes highly expressed in numerous pathological conditions and are considered attractive novel therapeutic targets in cancers [2,[9][10][11][12][13][14][15][16][17][18][19][20]. The amplification of NSD1 has been reported in multiple myeloma, lung cancer, neuroblastoma and glioblastoma.…”
Section: Introductionmentioning
confidence: 99%